From science to action: Advancing the Global Biodiversity Framework at SBSTTA-27 - Murillo, Adelaida L. (CGIAR System Organization, 2025)
This article reports on the 27th meeting of the Subsidiary Body on Scientific, Technical and Technological Advice (SBSTTA-27) held in Panama City as a key step in preparing for the upcoming Conference of the Parties (COP17) to the Convention on Biological Diversity. As biodiversity loss continues at alarming rates, the meeting brought together scientists, policymakers, and stakeholders to review progress in implementing the Kunming-Montreal Global Biodiversity Framework and identify pathways to accelerate action. Discussions at SBSTTA-27 emphasized the importance of integrated action across biodiversity, climate, and land agendas, and the need for science-based recommendations to guide decision-making for COP17. The meeting also highlighted the establishment of the new Subsidiary Body on Article 8(j), which focuses on Indigenous Peoples and local communities, and its role in embedding traditional knowledge into biodiversity governance. For the CGIAR Multifunctional Landscapes Science Program, SBSTTA-27 presented a strategic opportunity to align research and landscape approaches with global priorities that link biodiversity with food, land, and water systems